Keyholder to the Folksong Chests - Kadžytė, Gražina (Tautosakos darbai, 2020)
In the beginning of this year, the 100th anniversary of the folklore researcher Bronė Kazlauskienė (1920–2001) was celebrated at the Institute of Lithuanian Literature and Folklore. In the festive meeting organized for the occasion, folklorists of the Institute and Kazlauskienė’s family members shared their memories and discussed her scholarly works. Her professional activities were almost entirely devoted to research and publication of the Lithuanian folksongs. Having started her work in 1946 at the Folklore Department of the former Institute of Lithuanian History, she was among the first researchers attempting to define the structure of the Lithuanian folksong catalogue. From 1955, she continued this work at the Institute of Lithuanian Language and Literature, where she worked until 1994. Kazlauskienė presented her research results related to the creation of the folksong classification system in her theoretical and applied scientific works – research studies, articles, and folklore source publications. She edited for publication three books of the “Lithuanian Folksong Catalogue” and four volumes of the “Collection of Lithuanian Folksongs”. In 1994, along with other editors of this multivolume academic publication, she was awarded the Lithuanian National Science Award. However, her activities and publications dedicated to commemoration of prominent figures of Lithuanian culture and literature testify to still broader scholarly interests.
Keywords: -